Sonography of pleural space in healthy pregnants - preliminary results - Kocijančič, Igor (Radiology and oncology (Ljubljana), 2005)
Background. The purpose of our study was to determine the incidence of sonographically visible normal pleural fluid finding in healthy pregnants. Methods. Chest sonography was performed in 47 pregnant volunteers, searching for pleural fluid, first leaning on the elbow and than in a sitting position. 9-12 MHz linear probe was used. If the result of the first examination was positive (at least 2 mm thick anechoic layer), we repeated the procedure with 3-6 MHz large radius convex probe. Results. The fluid layer of typical wedge-shaped appearance was visible in the pleural space of 28/47 (59.5%) pregnant volunteers, on both sides in 18/47 (38.3%) and unilaterally in 10/47 (21.2%). The mean fhickness of fluid layer (mean of positive results in both positions) was 2.86 mm (SD 1.09 mm, range from 1.8 mm to 6.4 mm). More than 3 mm thick fluid layer was easily detected with 3-6 MHz abdominal convex probe in 7/47 (15%). Conclusions. Small amounts of pleural fluid can sometimes be detected by chest sonography, and hence also by abdominal sonography, in otherwise healthy pregnants. Such a positive result, if isolated, should not be taken as a sign of occult thoracic disease.
Keywords: human pregnancy; Nosečnost; Pleura; plevra; Pregnancy; Prsna mrena; Ultrasonography; ultrazvočna diagnostika